2015
DOI: 10.1038/ncomms9500
|View full text |Cite
|
Sign up to set email alerts
|

Nano-guided cell networks as conveyors of molecular communication

Abstract: Advances in nanotechnology have provided unprecedented physical means to sample molecular space. Living cells provide additional capability in that they identify molecules within complex environments and actuate function. We have merged cells with nanotechnology for an integrated molecular processing network. Here we show that an engineered cell consortium autonomously generates feedback to chemical cues. Moreover, abiotic components are readily assembled onto cells, enabling amplified and ‘binned' responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…sfGFP expression was tested in both MDAI2 and CT104 containing plasmid pCT6 and either pET‐sfGFP, pET‐sfGFP‐LsrK, or pET‐sfGFP‐LsrACDB for AI‐2 concentrations ranging from 0 to 40 μM (Figure ). As expected, both the number of fluorescing cells and the intensity of fluorescence were generally higher in CT104 than MDAI2 . The lack of AI‐2 degrading proteins likely allows prolonged activation of the lsr promoter resulting in measurable levels of sfGFP even in cells with low intracellular AI‐2 levels.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…sfGFP expression was tested in both MDAI2 and CT104 containing plasmid pCT6 and either pET‐sfGFP, pET‐sfGFP‐LsrK, or pET‐sfGFP‐LsrACDB for AI‐2 concentrations ranging from 0 to 40 μM (Figure ). As expected, both the number of fluorescing cells and the intensity of fluorescence were generally higher in CT104 than MDAI2 . The lack of AI‐2 degrading proteins likely allows prolonged activation of the lsr promoter resulting in measurable levels of sfGFP even in cells with low intracellular AI‐2 levels.…”
Section: Resultssupporting
confidence: 63%
“…Previously, we developed inducible AI‐2 controller cells with enhanced ability to uptake and respond to AI‐2 by manipulating the AI‐2 quorum sensing network through overexpression of proteins responsible for uptake and phosphorylation of AI‐2, specifically LsrACDB and LsrK . We have also engineered cells that autonomously activate protein expression based on accumulation of AI‐2 and demonstrated that deleting genes responsible for degrading and altering AI‐2, lsrF and lsrG , results in activation of protein expression at lower AI‐2 levels . In this paper, we demonstrate that combining these two strategies, use of an enhanced feedback loop through overexpression of LsrK and LsrACDB and deletion of lsrF and lsrG from the genome, can be used to engineer E. coli cells with enhanced sensitivity and ability to uptake and report on the presence of biologically relevant extracellular AI‐2 concentrations.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Humans Administration of SCFAs, LED209, tempol, AI-2, CAI-1 [18,19,26,[49][50][51][52][53]61] Treat or prevent disorders and diseases e.g. metabolic syndrome, obesity and cholera…”
Section: Signalling Moleculesmentioning
confidence: 99%
“…This opens exciting possibilities for implementing dynamical decision making using distributed SGNs. Terrel et al [34] also took a major step toward experimental implementation of distributed SGNs capable of classification. They demonstrated a system in which the presence of input was reported by a nanoparticle binding event that could occur only when two different cell types detected input signal.…”
Section: Intercellular Communication Between Synthetic Gene Networkmentioning
confidence: 99%